Comparative economics of maize grain and seed production in Okhaldhunga district, Nepal - Dulal, Puspa Raj; Marahatta, Santosh; Karn, Rupak (Journal of Agriculture and Natural Resources, 2020)
Maize cultivation is the one the major farm activities among Nepalese farmers. Basically, in the rural hills of Nepal like Okhaldhunga, it dominates any other crop production. The study was conducted for comparative assessment of economics, marketing and identification of major problems of maize seed and grain production in the hilly eastern district, Okhaldhunga during June of 2017. The data were obtained through the interview of 66 producers (33 each of maize grain and seed producers) with a pre-tested semi-structured questionnaire. Descriptive statistics and parametric tests (-test, t-test) were applied. Both the grain and the seed producers were similar in terms of socio-demographic characteristics, marketing accessibilities but the seed producers were significantly benefited from the training, the extension services, credit facilities despite having 0.14 ha lesser landholding than grain producers. The inputs (manures, fertilizers and the seed) contributed 48% and 50% of the total cost incurred for grain and seed production respectively and the pre-sowing and sowing activities contributed more than 77% of cost in both cases. Despite higher cost for seed production (NRs. 24,969 more than grain production), the benefit-cost ratio of seed production was found higher (1.31) than grain production (1.05). Only 24% of the total harvest was processed and marketed as seed and using optimum quantity (66% middle portion of the cob) for seed production could further increase the income by 23.35%, the improved B:C ratio being 1.51 . The major production problems were scarce farm labor followed by lack of infrastructures while low seasonal price followed by low volume of production ranked the first and second most important marketing related problems.